The influence of meteorological conditions and atmospheric circulation types on PM10 levels in western Turkey - AKKOYUNLU, BÜLENT OKTAY (SPRINGER, 2019)
High levels of atmospheric pollutants have been frequently measured in Turkey during the last decade. Specifically, the occurrence of these high particulate matter concentrations is often related to either local-scale conditions or regional-scale transport. In order to better understand the atmospheric factors that trigger poor air quality, further research investigating the relationship between air pollution and meteorological variables or atmospheric circulation patterns is needed. In this study, the influence of synoptic-scale weather types on PM10 levels over the Aegean region of Turkey is investigated for the period 2008-2015. First of all, hourly PM10 concentrations of 13 air quality stations are respectively converted to daily, seasonal, and regional averages. The seasonal variability of PM10 values in the region indicates that high particulate matter concentrations are registered in winter, fall, spring, and summer months with mean values at 90.6 (+/- 38.3 standard deviation), 66.9 (+/- 28.3), 61.6 (+/- 23.4), and 54.1 (+/- 12.8) g m(-3), respectively. In regard to the synoptic-scale approach, eight directional and two vorticity types of the Lamb weather type (LWT) method are used in the analysis. Based on the results, poor air quality conditions are observed in all seasons during active southeasterly (SE, interaction between a low pressure over Italy and a high pressure over the Caspian Sea) circulation types (CTs). In winter, mainly easterly (E), SE, southerly (S), and anticyclonic (A) weather patterns result in above normal PM10 concentrations. In addition to these four CTs, southwesterly (SW) types also cause higher PM10 values in the spring season. During summer, SE, SW, westerly (W), and cyclonic (C) CTs are associated with above-normal PM10 values. During fall, obvious higher PM10 concentrations are found during SE, S, and A types.
Keywords: Aegean; Circulation types; Lamb weather type; Turkey; PM10; REGIONAL TRANSPORT PATHWAYS; LONG-RANGE TRANSPORT; AIR-QUALITY; DUST TRANSPORT; PATTERNS; POLLUTION; WEATHER; CLASSIFICATION; PRECIPITATION; THESSALONIKI